Creative personality and authoral concept in А. Nurshayikov's prose (Eurasian Journal of Philology Science and Education, 2023)
This article deals with the problem of the concept of authorship in the representation of a creative person in the prose of the famous writer Azilkhan Nurshaikov.  Revealing the unique nature of creative personalities depicted in the artist's works from all sides, determining the artistic techniques and the author's concept used in describing their spiritual and human qualities, become the main directions and goals of the study.  The novel-interview "Truth and Legend", the story-monologue "Nine Feats", the essay "Two Memories", which have become the main object of research, prove with specific examples that they are works that reflect the author's concept and individual style.  In the depiction of such creative personalities as Bauyrzhan Momyshuly, Sabit Mukanov, Malik Gabdullin, Abdilda Tazhibaev, Mukhtar Auezov, talented writers of Kazakh literature, the factual and rational presentation by the author of what he saw in a rational narrative form is confirmed by contextual examples.  Explains the subjective and creative activity of the author in revealing the personality of a creative person as a result of scientific analysis.  The relevance of the study lies in expressing the skill of the writer, who managed to portray such qualities as greatness and individuality, common sense and wisdom, heroism and courage, nationalism and patriotism, kindness and brotherhood, rigor and exactingness, honesty and devotion, simplicity and sincerity inherent in the creative characters portrayed by the writer, with portrait-psychological characteristics and shows its importance.  Appeal to the theoretical study of the author's concept of foreign and domestic scientists who direct the research topic shows that this influenced the systematic solution of the problem considered in the article.